Anti-Extinction in the Tactile Modality. (June 2013) - White, Rebekah C; Davies, Anne M Aimola
Patients with extinction fail to report a contralesional stimulus when it is presented at the same time as an ipsilesional stimulus, and patients with unilateral neglect fail to report a contralesional stimulus even when there is no competing ipsilesional stimulus. Whereas extinction and neglect are common following stroke, the related phenomenon of anti-extinction is rare—there are four cases of anti-extinction in the literature, and all four cases demonstrated anti-extinction in the visual modality. Patients with anti-extinction do report a contralesional stimulus when it is presented at the same time as an ipsilesional stimulus; but, like patients with neglect, they fail to report a contralesional stimulus when there is no competing ipsilesional stimulus. We present the first case of anti-extinction in the tactile modality.